Technological surveillance and competitive intelligence for the funeral sector, case "grupo Obelisco Ltda." - Rodríguez-Parra, Rocío del Mar; González-Castro, Yolanda (Universidad Pedagógica y Tecnológica de Colombia, 2019)
This article shows the results obtained in the study called "Study of technological surveillance and competitive intelligence for the company Grupo Obelisco Ltda, which was oriented to the diversification of its service portfolio in the implementation of the final destination process. The described project was developed under the mixed (qualitative and quantitative) approach, through a descriptive study taking as a fundamental basis of its development the technological surveillance methodology called Innovitech. Through a specialized research, a limited scientific production could be identified in the face of emerging technologies in the disposal of human remains, becoming a little documented subject. Taking into account the characteristics of the company Grupo Obelisco Ltda., the trends of the sector and the research objective, it is concluded that within the technological trends the most viable are: biodegradable urn, alkaline hydrolysis process, cryo-drying and ecological cemetery.